Analisis Kelayakan Pengembangan Proyek Apartemen Citralake Suites - Citra Garden City - Noor Achyar Sulthoni; Anas Lutfi (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The population density in the capital has increased from year to years, this situation used by PT CD as a business tool in the property sector. A kind of research is needed to find out whether the development of this land is profitable or not, by conducting a Business Feasibility Analysis. Investment decision analysis is done by using 3 (three) main calculation methods. From the results of research conducted by the author, it is obtained as follows in :In the payback period, sales are up to 2018, reaching 60%, so this project is feasible to be acceptedNet Present Value Analysis, From the results of calculations, NPV cash inflow is still far greater than the NPV cash outflow means that according to the NPV assessment that this project is considered very feasible to be carried outThe Internal Rate of Return (IRR) is a feasible project because the IRR is a normal and optimistic alternative. greater than the Weighted average cost of capital (WACC)Based on the results of the analysis and calculations carried out by the author in relation to project, the general investment investment is considered very feasible and beneficial not only to the developer but also consumers who buy apartment units on the project. Paying attention to what has been analyzed and discussed, the author's suggestion is to re-check cashflow by considering finding alternative funding with an improved loan. so that the cost of capital is small and profits increase.